PHONEMIC PROCESSES THAT OCCUR IN THE TWITTER SOCIAL NETWORK - Azizah Manikandini; Agus Budi Wahyudi (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The development of language in social networks gives rise to many interesting forms to study. The purpose of this study is to describe the phonemic processes that occur in the Twitter social network. Research which is a type of qualitative research using the method of matching and dividing. As a result, there are 8 phonemic processes that occur in the Twitter social network in the form of zeronization (five apheresis, four syncope, three apocope), four metathesis, anaptysis (two prosthesis, three epenthesis, five paragog), and four neutralization. The author tends to eliminate the vowel phonemes /a/, /i/, and /e/ while the vowel phonemes /u/ and /o/ do not appear much, adding phonemes occurs to the vowel /a/, or the consonant phoneme which is the final phoneme in a say.